2008
DOI: 10.1111/j.1442-9071.2008.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular response analyser to assess hysteresis and corneal resistance factor in low tension, open angle glaucoma and ocular hypertension

Abstract: Hysteresis and CRF were highest in OHT eyes. These factors may prove to be useful measurements of ocular rigidity and may help to understand role of the corneal rigidity in monitoring the progress of conditions such as NTG, POAG and OHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
56
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 29 publications
10
56
1
2
Order By: Relevance
“…1,23 Conversely, it has been suggested that low CH might be expected to increase the risk for developing glaucomatous optic neuropathy, possibly due to reduced capacity of the eyewall to dampen IOP spikes 23,24 and/or reduced ability of optic nerve structures to suitably respond to IOP fluctuations. 1,25,26 This premise is supported by several studies, which indicate that eyes with POAG exhibit lower CH compared with normal eyes [1][2][3][12][13][14][15][16] and eyes with OH. 1,12 In addition, lower CH has been linked to both glaucoma progression 17,18 and severity.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…1,23 Conversely, it has been suggested that low CH might be expected to increase the risk for developing glaucomatous optic neuropathy, possibly due to reduced capacity of the eyewall to dampen IOP spikes 23,24 and/or reduced ability of optic nerve structures to suitably respond to IOP fluctuations. 1,25,26 This premise is supported by several studies, which indicate that eyes with POAG exhibit lower CH compared with normal eyes [1][2][3][12][13][14][15][16] and eyes with OH. 1,12 In addition, lower CH has been linked to both glaucoma progression 17,18 and severity.…”
Section: Introductionsupporting
confidence: 66%
“…These findings are consistent with other reports and underline the diagnostic promise as well as the shortcomings associated with CH. 1,12,16 After the study sample was divided into CCT tertiles, however, CH differences between POAG and OH were better delineated as shown in Figure 1. Specifically, while some overlap remained, the CH ranges within the subgroups appeared smaller for both POAG and OH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corneal hysteresis may vary from different subjects. Sunil et al reported that corneal hysteresis was lowest in NTG eyes when comparing with POAG and OHT eyes [3]. On the other hand, Ang GS reported a small but statistically higher mean CH in NTG eyes than POAG eyes [4].…”
mentioning
confidence: 96%